Penerapan Metode Demonstrasi Untuk Meningkatkan Keterampilan Sport Massage Pada Mahasiswa Pendidikan Jasmani - Parengkuan, Meyke (Universitas Negeri Gorontalo, 2025)
This study aims to improve the sport massage skills of Physical Education students through the application of the demonstration method. The research employed a Classroom Action Research (CAR) approach conducted in two cycles. The subjects were 24 students enrolled in a Physical Training course at a state university. Each cycle consisted of planning, action implementation, observation, and reflection stages. Research instruments included skill observation sheets, field notes, and documentation. The results indicated a significant improvement in students’ sport massage skills, with the mastery percentage increasing from 54.17% in the pre-cycle to 79.17% in cycle I, and reaching 95.83% in cycle II. This improvement was attributed to the clarity of movement visualization provided through direct demonstrations by the lecturer, which enabled students to understand the techniques accurately and minimize movement errors. The study recommends the use of demonstration methods in teaching practical skills in Physical Education, particularly sport massage.